Inspection Based Probabilistic Modeling of Fatigue Crack Progression. (2016) - Krejsa, M.; Kala, Z.; Seitl, S.
Abstract: Attention to the fatigue cracks in steel structures and bridges has been paid for a long time. Fatigue crack damage depends on a number of stress range cycles. Three sizes are important for the characteristics of the propagation of fatigue cracks - the initial size, detectable size and acceptable size. The theoretical model of fatigue crack progression in paper is based on a linear fracture mechanics. When determining the required degree of reliability, it is possible to specify the time of the first inspection of the construction which will focus on the fatigue damage. Using a conditional probability, times for subsequent inspections can be determined. For probabilistic calculation of fatigue crack progression was used the original and new probabilistic methods - the Direct Optimized Probabilistic Calculation ("DOProC"), which uses a purely numerical approach without any simulation or approximation techniques. The algorithm of the probabilistic calculation was applied in the FCProbCalc code ("Fatigue Crack Probabilistic Calculation"), using which is possible to carry out the probabilistic modelling of propagation of fatigue cracks in a user friendly environment very effectively.